Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/09291016.2015.1073477
|View full text |Cite
|
Sign up to set email alerts
|

Does post-warm-up rest interval affect the diurnal variation of 30-s Wingate cycle ergometry?

Abstract: The purpose of this investigation was to assess the effects of rest interval following active warm-up (WU) durations on the diurnal variation of high-intensity cycling performance. Eleven male physical education students (22.6 ± 2.5 years; 179.2 ± 5.7 cm; 82.6 ± 9.6 kg; mean ± SD) participated in a cross-over randomized study, and they all underwent the 30-s Wingate test in the morning (08:00 h) and in the evening (18:00 h), after 5-min (WU 5 ) and 15-min (WU 15 ) warm-up durations, either with rest (WR), or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Moreover, the present study findings support previous researches investigating the effects of WU durations on high-intensity cycling performances reinforcing the importance of increasing the WU duration up to 15 min to reach higher morning cycling performances [16,17,34]. Others, suggested to reduce WU duration for intermediate and intermittent events when undertaken in hot climatic condition, to avoid an excessive increase in whole-body temperature [1].…”
Section: Power-output (Mp and Pp) And Core Temperatures (T Tym And Mbt)supporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, the present study findings support previous researches investigating the effects of WU durations on high-intensity cycling performances reinforcing the importance of increasing the WU duration up to 15 min to reach higher morning cycling performances [16,17,34]. Others, suggested to reduce WU duration for intermediate and intermittent events when undertaken in hot climatic condition, to avoid an excessive increase in whole-body temperature [1].…”
Section: Power-output (Mp and Pp) And Core Temperatures (T Tym And Mbt)supporting
confidence: 90%
“…Several studies reported no effect of WU duration on fatigue index (FI) computed after the 30 s Wingate-test with or without a recovery rest interval separating it to performance [ 16 , 17 , 37 ]. However, it was shown recently, that 15 and 20 min cycling warm-up (at 50% of MAP) induce higher RPE and FI values during 30 s Wingate-test when compared to 5 min duration in physical education students [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not in line with Mussi (2018) who investigated the effects of CWI and AR application on BT and found no significant difference between CWI and AR in temperature. Chaâri et al (2015) study demonstrated that a 5-min post-warm-up rest interval did not generate a drop in core temperature and help to maintain an elevated state of preparedness, which has a direct impact on the subsequent high-intensity cycling performance. Immersion in water and cold application causes a decrease in body temperature.…”
Section: Passive Recoverymentioning
confidence: 82%